Incidence and risk factors related to fear of falling during the first mobilisation after total knee arthroplasty among older patients with knee osteoarthritis: A cross‐sectional study. Issue 17 (20th June 2021) - Zhang, Huaguo; Si, Wenteng; Pi, Hongying
Abstract: Background: The factors that lead to the fear of falling among older people after total knee arthroplasty (TKA) are poorly understood. The present study aims to examine the fear of falling among such patients and to determine the factors that are associated with that fear. Methods: A total of 285 patients aged ≥65 with knee osteoarthritis who underwent TKA at an orthopaedic hospital between November 2019 and May 2020 completed surveys about their own first mobilisation after TKA. They were asked to indicate whether they were afraid of falling by asking a single question, and what their pain level was on a visual analogue scale. They also completed the General Anxiety Disorder scale, the Geriatric Depression Scale–Short Form and the Social Support Rating Scale. Multivariate logistic regression was used to identify risk factors for fear of falling during the first mobilisation after TKA. This study was reported in compliance with the STROBE checklist for cross‐sectional studies (see Supplementary File S1 ). Results: Just over half (56.5%) of participants reported being afraid of falling. Multivariate logistic regression identified three independent risk factors that explained a total of 31% of the variance in the fear of falling: female sex (odds ratio (OR) = 4.21, 95% confidence interval (CI) = 2.35–7.55), higher body mass index (OR =3.93, 95% CI =1.53–10.10) and higher anxiety (OR = 1.56, 95% CI = 1.37–1.78). Conclusions: Many older patients fear falling when they begin to move after TKA, particularly women and those with higher body mass index or anxiety. These subgroups may merit special attention from healthcare professionals to mitigate their fears and optimise recovery after TKA.